Comparative Study of Two Acid Digestion Protocols for Evaluating Potentially Toxic Elements in Surface Sediments Influenced by Sewage Discharge and Sand Mining Activity - Asare, E.A. (Springer, 2022)
The study aimed to compare two acid digestion techniques, the partial digestion (total-recoverable) protocol by USEPA 3051 (HNO3) and total digestion (total-total) method by Hossner (Methods of soil analysis: Part 3. Chemical methods, SSSA and ASA, Madison, pp 49–64, 1996), to recommend an efficient method for evaluating ten potentially toxic elements (PTEs) (i.e., As, Pb, Cu, Cd, Mn, Zn, Cr, Ni, Co, and Fe) concentrations in surface sediments influenced by sewage discharge and sand mining activity. Inductively coupled plasma-optical emission spectroscopy (ICP-OES) analyzed the PTEs after sample treatment and extraction. The hot plate Hossner method exhibited high PTEs extractability than the microwave-assisted USEPA 3051 method. Generally, As, Pb, Cu, Cd, Mn, Zn, and Cr extracted by both methods depicted sediment background concentrations. No significant differences in concentrations between the two digestion techniques for Ni, Co, and Fe were observed in all samples. Furthermore, lower negative biases were observed between the two digestion techniques for extracting Ni, Co, and Fe in all sediment samples. Also, positive correlations between the total-recovery protocol and the total-total method were observed for Ni, Co, and Fe concentrations in all study sites. This implied that both total-recoverable and total-total methods were efficiently extracted Ni, Co, and Fe in all sediment samples. In addition, the total-recoverable method partially extracted other PTEs in the sediment samples, unlike the total-total technique. The total-recoverable (USEPA 3051) method can be recommended for extracting PTEs in sediment samples originating from lithogenic sources on the condition of using a strong acid such as HF or strong acids combination. The study revealed that sediment physicochemical characteristics influence the extraction of PTEs in sediment. Therefore, sediment factors should be considered when selecting incomplete acid digestion methods for extracting PTEs.
Research Article
Keywords: Agona Abodom; Sediment; Potentially toxic elements; Hossner method; USEPA 3051 method